Chapter Sedimentological consequences of Posidonia Oceanica banquette removal: Sakarun beach case study (Dugi otok, Croatia) - Godec, Petra (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Removal of Posidonia oceanica banquettes from Sakarun beach (Dugi otok Island, Croatia) was a common practice to increase recreational use during the summer tourist season. The sandy part of the beach showed gradual erosion and has partially disappeared. Geological and geomorphological were conducted over nine-month period to investigate the relationship between the banquette removal and sediment loss. The results indicate that the continuous removal of sediment-laden posidonia banquette may cause a deficit in the beach sediment budget, the effects of which may not become apparent until several-year delay.